Diamond Radiation Detector with Built‐In Boron‐Doped Neutron Converter Layer. Issue 3 (5th February 2022) - Miyake, Taku; Nakagawa, Hisaya; Masuzawa, Tomoaki; Yamada, Takatoshi; Nakano, Takayuki; Takagi, Katsuyuki; Aoki, Toru; Mimura, Hidenori
Abstract : Diamond Radiation Detector Neutron, a promising probe for bioimaging and non‐destructive inspection, demands high efficiency flat‐panel detector for imaging applications. Polycrystalline diamond is a material of choice, with built‐in neutron converter formed by boron doping and scalability to wide‐area image sensor. More information can be found in article number 2100315 by Tomoaki Masuzawa and co‐workers.